2012
DOI: 10.1111/hae.12075
|View full text |Cite
|
Sign up to set email alerts
|

No inhibitor development after continuous infusion of factor concentrates in subjects with bleeding disorders undergoing surgery: a prospective study

Abstract: Inhibitor development against von Willebrand factor, factor VIII or factor IX is one of the most severe complications of treating patients with von Willebrand's disease (VWD), haemophilia A or haemophilia B respectively. Continuous infusion of factor concentrate has been implicated as a risk factor for inhibitor development. This prospective study investigated inhibitor development after continuous infusion of factor concentrate for surgical procedures in subjects with VWD or a severe form of haemophilia (fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
2
18
0
2
Order By: Relevance
“…At the end of the study, none of the patients had developed inhibitors to FVIII; yet, all had over 150 EDs to FVIII and no documented history of inhibitors at enrolment. Similarly, other studies have reported no de novo inhibitors for FVIII‐experienced patients who received rFVIII as CI during surgery , and a review of summary data for FVIII in over 70 surgeries in previously treated patients found no reports of inhibitor development . One limitation of this study is that inhibitor tests from some patients are missing, as they might have been considered low‐risk patients and therefore not been more often tested in usual practice.…”
Section: Discussionmentioning
confidence: 76%
“…At the end of the study, none of the patients had developed inhibitors to FVIII; yet, all had over 150 EDs to FVIII and no documented history of inhibitors at enrolment. Similarly, other studies have reported no de novo inhibitors for FVIII‐experienced patients who received rFVIII as CI during surgery , and a review of summary data for FVIII in over 70 surgeries in previously treated patients found no reports of inhibitor development . One limitation of this study is that inhibitor tests from some patients are missing, as they might have been considered low‐risk patients and therefore not been more often tested in usual practice.…”
Section: Discussionmentioning
confidence: 76%
“…Factor replacement can be administered via continuous infusion or intravenous bolus infusion [13]. In this study, intravenous bolus infusion was the route of administration in all operations when factor concentrate was used.…”
Section: Discussionmentioning
confidence: 99%
“…The most challenging complication was the development of inhibitors in PwH preoperatively not considered for this situation, imposing the change of replacement therapy to a prohibitive therapy, difficult to access because of the costs (22). It seemed not to be connected with the factor concentrate or the modality of factor concentrate administration (bolus vs. infusion, plasma derived vs recombinant) (23). It is difficult to answer the question regarding the responsible factor or condition for inhibitor formation.…”
Section: Discussion Conclusionmentioning
confidence: 99%